Nilai Pendidikan Hindu Dalam Situs Bukit Batu Bagi Masyarakat Hindu Di Kabupaten Katingan - Piogenta Piogenta; I Ketut Subagiasta; Mujiyono Mujiyono (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2022)
Bukit Batu Site has an extraordinary uniqueness, because each structure is formed from other stone structures that have their own names and functions as well as mythology. The uniqueness can be seen from the beginning when you enter the rocky area of ​​the Bukit Batu Site, which has a sacred lake and ends with a large, tall stone, the Tingkes stone. The community understands the Bukit Batu Site as a tourist attraction for recreation, but actually has values ​​derived from mythology, the structure of the Bukit Batu Site, community social activities and religious activities. Researchers are interested in studying the value of Hindu education in the Bukit Batu Site for the Hindu community in Katingan Regency. The theory used is the theory of value. This research is a field research with qualitative descriptive analysis, with an emic approach. The data collection techniques used are observation, interview, library studies, and documentation studies, from primary and qualitative data. Qualitative data analysis techniques are carried out by reducing data, drawing conclusions, and presenting data The results of the research analyzed show that the value of Hindu education at the Bukit Batu Site for the Hindu community in Katingan Regency is the value of tatwa education (philosophy), the value of moral education (ethics), the value of ceremonial education, and the value of mutual cooperation education. When visiting and participating in religious activities at the Bukit Batu Site, it will naturally transform the values ​​of Hindu education so that it will increase the sradha and devotion of Hindus. The Bukit Batu Site in Katingan Regency has a high existence in the social, religious, and educational life of Hindus, which will mature the community